2014
DOI: 10.1158/1541-7786.mcr-14-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Response of Indole-3-Carbinol in Human Melanoma Cells Is Triggered by an Interaction with NEDD4-1 and Disruption of Wild-Type PTEN Degradation

Abstract: Human melanoma cells displaying distinct PTEN genotypes were used to assess the cellular role of this important tumor suppressor protein during the anti-proliferative response induced by the chemopreventative agent indole-3-carbinol (I3C), a natural indolecarbinol compound derived from the breakdown of glucobrassicin produced in cruciferous vegetables such as broccoli and Brussels sprouts. I3C induced a G1-phase cell cycle arrest and apoptosis by stabilization of PTEN in human melanoma cells that express wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…Many natural compounds are also reported to inactivate the PI3K-AKT pathway either by activating PTEN or inactivating oncogenes that drive AKT activation. For example, the chemopreventive agent indole-3-carbinol (I3C), a natural indolecarbinol compound derived from the breakdown of glucobrassicin produced in cruciferous vegetables such as broccoli and Brussels sprouts, induced G1-phase cell-cycle arrest and apoptosis and inhibited the in vivo tumor growth rate by stabilization of PTEN in human melanoma cells that express wild-type PTEN, but not in cells with mutant or null PTEN genotypes [276]. Curcumin treatment significantly resulted in the inhibition of cell proliferation and an increase in the apoptosis rate through the upregulation of PTEN associated with a decrease in DNA methylation level via downregulation of DNMT3b in vivo and in vitro [277].…”
Section: Prophylactic and Therapeutic Potential Of Targeting Anti-mentioning
confidence: 99%
“…Many natural compounds are also reported to inactivate the PI3K-AKT pathway either by activating PTEN or inactivating oncogenes that drive AKT activation. For example, the chemopreventive agent indole-3-carbinol (I3C), a natural indolecarbinol compound derived from the breakdown of glucobrassicin produced in cruciferous vegetables such as broccoli and Brussels sprouts, induced G1-phase cell-cycle arrest and apoptosis and inhibited the in vivo tumor growth rate by stabilization of PTEN in human melanoma cells that express wild-type PTEN, but not in cells with mutant or null PTEN genotypes [276]. Curcumin treatment significantly resulted in the inhibition of cell proliferation and an increase in the apoptosis rate through the upregulation of PTEN associated with a decrease in DNA methylation level via downregulation of DNMT3b in vivo and in vitro [277].…”
Section: Prophylactic and Therapeutic Potential Of Targeting Anti-mentioning
confidence: 99%
“…Another study found that I3C induces apoptosis in SK-MEL-5 melanoma cells by down-regulation of MITF [326]. Furthermore, I3C-mediated anti-proliferative effect was through interaction with neuronal precursor cell-expressed developmentally down regulated 4 and wild-type PTEN degradation in human melanoma cells [327]. I3C consumption was also associated with increased sensitivity to chemotherapy in a study of mice with B16 melanoma [328].…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
“…In clinical trials, I3C was tolerated well with minimal side effects (Reed et al, 2005). From a mechanistic viewpoint, we have established that the presence of specific I3C target proteins expressed in human cancer cells, such as Human Neutrophil Elastase (Nguyen et al, 2008, Aronchik et al, 2010, Aronchik et al, 2012) in breast cancer and the Neural precursor cell Expressed Developmentally Down-regulated 4 (NEDD4-1) a ubiquitin ligase whose function is critical in a subset of melanoma genotypes (Aronchik et al, 2014). We recently observed that I3C strongly inhibits oncogenic BRAF enzymatic activity with little effect on the wild type enzyme under conditions in this indolecarbinol disrupts proliferation of oncogenic BRAF-expressing melanoma cells (Kundu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, ectopic application of I3C directly inhibits skin tumor formation in mouse models (Srivastava and Shukla, 1998). We have observed that human melanoma cells with distinct mutational profiles are sensitive to the anti-proliferative effects of I3C (Aronchik et al, 2014), suggesting that this natural phytochemical could provide one component of a combinational therapy for human melanomas.…”
Section: Introductionmentioning
confidence: 99%